2021
DOI: 10.1182/blood.2021012021
|View full text |Cite|
|
Sign up to set email alerts
|

Belumosudil for chronic graft-versus-host disease after 2 or more prior lines of therapy: the ROCKstar Study

Abstract: Belumosudil, an investigational oral selective inhibitor of rho-associated coiled-coil-containing protein kinase-2 (ROCK2), reduces type 17 and follicular helper T cells via downregulation of signal transducer and activator of transcription 3 (STAT3) and enhances regulatory T cells via upregulation of signal transducer and activator of transcription 5 (STAT5). Belumosudil may effectively treat patients with cGVHD, a major cause of morbidity and late nonrelapse mortality after an allogeneic hematopoietic cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(101 citation statements)
references
References 35 publications
5
96
0
Order By: Relevance
“…The efficacy of belumosudil for the treatment of cGVHD was demonstrated in the randomized, multicentre, phase II ROCKstar trial in allogeneic haematopoietic cell transplant (alloHCT) recipients (NCT03640481) [ 14 ]. After a median follow-up of 14 months, the best overall response rate (ORR, defined as complete response or partial response; primary endpoint) was 74% (95% CI 62–84%) with belumosudil 200 mg once daily and 77% (95% CI 65–87%) with belumosudil 200 mg twice daily.…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of belumosudil for the treatment of cGVHD was demonstrated in the randomized, multicentre, phase II ROCKstar trial in allogeneic haematopoietic cell transplant (alloHCT) recipients (NCT03640481) [ 14 ]. After a median follow-up of 14 months, the best overall response rate (ORR, defined as complete response or partial response; primary endpoint) was 74% (95% CI 62–84%) with belumosudil 200 mg once daily and 77% (95% CI 65–87%) with belumosudil 200 mg twice daily.…”
Section: Scientific Summarymentioning
confidence: 99%
“…The overall failure-free survival (FFS) rate was 75% at 6 months and 56% at 12 months. The overall survival (OS) rate at 2 years was 89% [ 14 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…Responses were clinically meaningful, with a median duration of response of 35 weeks, and were associated with quality-of-life improvements and corticosteroid (CS) dose reductions (86). Furthermore, the ROCKstar study showed that belumosudil showed responses for cGVHD after 2 or more prior lines of therapy (87). Based on these findings, belumosudil was recently FDA approved for patients 12 years and older who have received 2 or more prior lines of therapy (88).…”
Section: Th17 and Tc17mentioning
confidence: 99%
“…However, these studies evaluated those 12 years of age or older; studies evaluating effectiveness/dosing in children younger than 12 and dosing are ongoing (81,83). Other agents that are currently under investigation include belumosudil and ibrutinib, though further investigation is needed for use in pediatrics (84,85). Despite aggressive treatment, most patients have acute flares with mortality rate being between 12% and 27% at 5 years due to secondary infection or respiratory complications (8,51,78).…”
Section: Bronchiolitis Obliteransmentioning
confidence: 99%